Syarat Kesehatan Fisik Bagi Calon Presiden dalam Perspektif Politik Islam dan Politik Indonesia - Mujar Ibnu Syarif (Universitas Islam Negeri Jakarta, 2017)
This article specifically discusses the important issues on physical health requirements for presidential candidates in Islamic and Indonesian perspectives. This article presents two important conclusions as follows: first, in the Islamic perspective, the majority of scholars argue that a person whoi s physically less or unhealthy cannot be elected as president. The result of comparison analysis of Islamic perspective and Indonesian perspective shows some similarities. First, the importance of a presidential candidate meets the criteria of physical health. Second, the disease is a serious illness that isallegedly able to disrupt the implementation of his/her duties and obligations as president. DOI: 10.15408/ajis.v17i1.6230